2017
DOI: 10.1039/c7cc05834a
|View full text |Cite
|
Sign up to set email alerts
|

A two-photon fluorescent probe for ratiometric imaging of endogenous hypochlorous acid in live cells and tissues

Abstract: A fluorescent probe that enables ratiometric imaging of endogenous hypochlorous acid (HOCl) in cells and tissues by two-photon microscopy is developed based on a red-emitting acetyl-benzocoumarin (AcBC) dye. An oxathiolane group in the probe reacts with HOCl to generate the AcBC dye, which involves a ratiometric fluorescence change only toward HOCl along with high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…have been developed for imaging HClO in live cells (30)(31)(32)(33)(34)(35)(36). With these probes, visualization of HClO in wounded tissues or an inflammatory mouse model has been achieved (35,37). However, there has been no report on direct real-time visualization of HClO fluxes in the brain of live animals, especially during epileptic seizures.…”
Section: Significancementioning
confidence: 99%
“…have been developed for imaging HClO in live cells (30)(31)(32)(33)(34)(35)(36). With these probes, visualization of HClO in wounded tissues or an inflammatory mouse model has been achieved (35,37). However, there has been no report on direct real-time visualization of HClO fluxes in the brain of live animals, especially during epileptic seizures.…”
Section: Significancementioning
confidence: 99%
“…However, the detection of endogenous HOCl is a challenging task due to the low biological concentration, a short lifetime, and a strong oxidizing property [ 43 ]. In 2017, Ahn et al reported a benzo[ g ]coumarin-based ratiometric probe for endogenous HOCl imaging in live cells and tissues ( 31 ; Figure 10 ) [ 21 ]. An oxathiolane group is substituted at the electron-withdrawing position, and the deprotection into acetyl of this moiety by HOCl causes the intramolecular charge-transfer (ICT) character change of the benzo[ g ]coumarin dye in a ratiometric manner: emission maximum shift from 598 nm (with 424 nm absorption maximum) to 633 nm (with 598 nm absorption maximum).…”
Section: Benzo[ G ]Coumarins For Fluorescent Prmentioning
confidence: 99%
“…The probe based on the red-emitting acetyl-benzocoumarin (AcBC) dye wiithin the probe, oxathiolane group was attached in orderf or it to react with HOCl. [127] Reaction with HOCl will trigger the ring opening reactiono ft hiolactone and whichi nvolves ar atiometric fluorescencec hange only toward HOCl along with high sensitivity.F urther studies reveal that the probe can be used to image HOCl in living HeLa cells.…”
Section: Scheme115 Anthracene Basedp Robe For Hocl Detectionmentioning
confidence: 99%
“…The Ahn group in 2017 developed a fluorescent probe that enables ratiometric imaging of endogenous hypochlorous acid (HOCl) in cells and tissues by way of two‐photon microscopy (Scheme ). The probe based on the red‐emitting acetyl‐benzocoumarin (AcBC) dye wiithin the probe, oxathiolane group was attached in order for it to react with HOCl . Reaction with HOCl will trigger the ring opening reaction of thiolactone and which involves a ratiometric fluorescence change only toward HOCl along with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%